2017
DOI: 10.1007/s10068-017-0074-6
|View full text |Cite
|
Sign up to set email alerts
|

Decline pattern and risk assessment of cyenopyrafen in different varieties of Asian pear using liquid chromatography and tandem mass spectrometry

Abstract: The dissipation pattern of a commercial cyenopyrafen formulation sprayed at the recommended dose on Asian pears (two different species) grown at two different sites was investigated using liquid chromatography-ultraviolet detection. Samples collected randomly over 14 days were extracted using acetone, partitioned using -hexane/dichloromethane (8/2, v/v), and purified using a Florisil solidphase extraction cartridge. The residues in field-incurred samples were confirmed via liquid chromatography-tandem mass spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The half-lives of chlorfenapyr estimated in this study were similar to or slightly lower than those reported in previous studies on strawberries (4.68 days), sweet persimmons (8.8 days), and various vegetables (1.2–9.8 days) [ 7 , 16 , 28 , 29 ]. The half-lives of cyenopyrafen were previously reported to be 5.2–9.8 days in Asian pears [ 30 ] and 7.99–12.65 days in grapes [ 31 ], which are similar to our current study. The half-lives of indoxacarb were reported to be 3.0–3.8 days in eggplants, 3.12–3.21 days in tomatoes, 3.46–4.77 in green chilis, 7.4–8.4 days in pomegranate fruits, and ranging from 20 to 24 days in apples [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The half-lives of chlorfenapyr estimated in this study were similar to or slightly lower than those reported in previous studies on strawberries (4.68 days), sweet persimmons (8.8 days), and various vegetables (1.2–9.8 days) [ 7 , 16 , 28 , 29 ]. The half-lives of cyenopyrafen were previously reported to be 5.2–9.8 days in Asian pears [ 30 ] and 7.99–12.65 days in grapes [ 31 ], which are similar to our current study. The half-lives of indoxacarb were reported to be 3.0–3.8 days in eggplants, 3.12–3.21 days in tomatoes, 3.46–4.77 in green chilis, 7.4–8.4 days in pomegranate fruits, and ranging from 20 to 24 days in apples [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Resultssupporting
confidence: 92%
“…The half-lives of spirotetramat were reported as 1.30–1.90 days in chilis, 5.6–7.6 days in grapes, and 4.7–9.6 days in citrus, which are shorter than those observed in this study [ 37 , 38 , 39 , 40 ]. These results suggest that many factors could influence the degradation of pesticides, such as their physical and chemical properties, environmental conditions, crop species, and growth dilution factors [ 30 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tandem mass spectrometry is a selective and sensitive technique than can identify the compound based on molecular structure, compared with the false positive results of a conventional LC detector (Kabir, Abd El‐Aty, Kim, et al, ). Mass confirmation was determined using tandem mass spectrometry (LC–MS/MS) to justify the dimethomorph peak obtained from LC‐UVD.…”
Section: Resultsmentioning
confidence: 99%
“…The acceptable daily intake (ADI) of sulfoxaflor is 0.051 mg (Table ). The estimated daily intake can be calculated from the following equation: Estimated daily intake (EDI) = residue amount × average uptake (Kabir et al, ; Lee et al, ) ADI0.25em()%=EDI/ADI×100 …”
Section: Resultsmentioning
confidence: 99%